Change and Validity Analysis in Deductive Program Verification - Jakobs, Marie-Christine

Brief Announcement: SplayNets - Towards Self-Adjusting Distributed Data Structures - Schmid, Stefan; Avin, Chen; Scheideler, Christian; Häupler, Bernhard; Lotker, Zvi (Proceedings of the 26th International Symposium on Distributed Computing (DISC))
This paper initiates the study of self-adjusting distributed data structures for networks. In particular, we present SplayNets: a binary search tree based network that is self-adjusting to routing request.We derive entropy bounds on the amortized routing cost and show that our splaying algorithm has some interesting properties.

Multi-Modal, Multi-Touch Interaction with Maps in Disaster Management Applications - Paelke, Volker; Nebe, Karsten; Geiger, Christian; Klompmaker, Florian; Fischer, Holger Gerhard (ISPRS - International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)

Brief Announcement: Hashed Predecessor Patricia Trie - A Data Structure for Efficient Predecessor Queries in Peer-to-Peer Systems - Kniesburges, Sebastian; Scheideler, Christian (Proceedings of the 26th International Symposium on Distributed Computing (DISC))
The design of ecient search structures for peer-to-peer systems has attracted a lot of attention in recent years. In this announcement we address the problem of nding the predecessor in a key set and present an ecient data structure called hashed Predecessor Patricia trie. Our hashed Predecessor Patricia trie supports PredecessorSearch(x) and Insert(x) and Delete(x) in O(log log u) hash table accesses when u is the size of the universe of the keys. That is the costs only depend on u and not the size of the data structure. One feature of our approach is that it only uses the lookup interface of the hash table and therefore hash table accesses may be realized by any distributed hash table (DHT).

Block Abstraction Memoization for CPAchecker - Wonisch, Daniel (Proceedings of the 18th International Conference on Tools and Algorithms for the Construction and Analysis of Systems (TACAS))
Block Abstraction Memoization (ABM) is a technique in software model checking that exploits the modularity of programs during verification by caching. To this end, ABM records the results of block analyses and reuses them if possible when revisiting the same block again. In this paper we present an implementation of ABM into the predicate-analysis component of the software-verification framework CPAchecker. With our participation at the Competition on Software Verification we aim at providing evidence that ABM can not only substantially increase the efficiency of predicate analysis but also enables verification of a wider range of programs.

Diversität, Konflikte und Leistung in Teams: Ein meta-analytisches Strukturgleichungsmodell - Schneid, M; Steinmetz, Holger; Isidor, R; Kabst, Rüdiger

Endogeneity in the behavioral sciences: An illustration with real data - Kabst, Rüdiger

Basic Network Creation Games with Communication Interests - Cord-Landwehr, Andreas; Huellmann (married name: Eikel), Martina; Kling, Peter; Setzer, Alexander (Proceedings of the 5th International Symposium on Algorithmic Game Theory (SAGT))
Network creation games model the creation and usage costs of networks formed by a set of selfish peers.Each peer has the ability to change the network in a limited way, e.g., by creating or deleting incident links.In doing so, a peer can reduce its individual communication cost.Typically, these costs are modeled by the maximum or average distance in the network.We introduce a generalized version of the basic network creation game (BNCG).In the BNCG (by Alon et al., SPAA 2010), each peer may replace one of its incident links by a link to an arbitrary peer.This is done in a selfish way in order to minimize either the maximum or average distance to all other peers.That is, each peer works towards a network structure that allows himself to communicate efficiently with all other peers.However, participants of large networks are seldom interested in all peers.Rather, they want to communicate efficiently with a small subset only.Our model incorporates these (communication) interests explicitly.Given peers with interests and a communication network forming a tree, we prove several results on the structure and quality of equilibria in our model.We focus on the MAX-version, i.e., each node tries to minimize the maximum distance to nodes it is interested in, and give an upper bound of O(\sqrt(n)) for the private costs in an equilibrium of n peers.Moreover, we give an equilibrium for a circular interest graph where a node has private cost Omega(\sqrt(n)), showing that our bound is tight.This example can be extended such that we get a tight bound of Theta(\sqrt(n)) for the price of anarchy.For the case of general networks we show the price of anarchy to be Theta(n).Additionally, we prove an interesting connection between a maximum independent set in the interest graph and the private costs of the peers.

Recruitment Process Outsourcing and Applicant Reactions: Does Image Make a Difference? - Wehner, M C; Giardini, A; Kabst, Rüdiger

Designing Multi-Modal Map-Based Interfaces for Disaster Management - Paelke, Volker; Nebe, Karsten; Geiger, Christian; Klompmaker, Florian; Fischer, Holger Gerhard (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI))

Authenticated Tangible Interaction using RFID and Depth-Sensing Cameras - Supporting Collaboration on Interactive Tabletops - Klompmaker, Florian; Fischer, Holger Gerhard; Jung, Helge (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI))

Integrating usability engineering in the software development lifecycle based on international standards - Fischer, Holger Gerhard (Proceedings of the 4th ACM SIGCHI symposium on Engineering interactive computing systems - EICS '12)

Attribute-basierte Verschlüsselung - Schleiter, Patrick

Enriching Disaster Control Management based on Human-Computer Design - Fischer, Holger Gerhard; Klompmaker, Florian (Proceedings of the 9th International Conference on Information Systems for Crisis Response and Management (ISCRAM))

Der Qualitätsstandard für Usability Engineering der German UPA – Aktueller Stand der Arbeiten - Fischer, Holger Gerhard; Geis, Thomas; Kluge, Oliver; Bogner, Christian; Polkehn, Knut (Jahresband Usability Professionals)

Archimetrix: Improved Software Architecture Recovery in the Presence of Design Deficiencies - Platenius, Marie Christin; von Detten, Markus; Becker, Steffen (Proceedings of the 16th European Conference on Software Maintenance and Reengineering (CSMR))
Maintaining software systems requires up-to-date models of these systems to systematically plan, analyse and execute the necessary reengineering steps. Often, no or only outdated models of such systems exist. Thus, a reverse engineering step is needed that recovers the system’s components, subsystems and connectors. However, reverse engineering methods are severely impacted by design deficiencies in the system’s code base, e.g., they lead to wrong component structures. Several approaches exist today for the reverse engineering of component-based systems, however, none of them explicitly integrates a systematic design deficiency removal into the process to improve the quality of the reverse engineered architecture. Therefore, in our Archimetrix approach, we propose to regard the most relevant deficiencies with respect to the reverse engineered component-based architecture and support reengineers by presenting the architectural consequences of removing a given deficiency. We validate our approach on the Common Component Modeling Example and show that we are able to identify relevant deficiencies and that their removal leads to an improved reengineered architecture.

Archimetrix: A Tool for Deficiency-Aware Software Architecture Reconstruction - von Detten, Markus (Proceedings of the 19th Working Conference on Reverse Engineering (WCRE))
Maintaining software systems requires up-to-date models of these systems to systematically plan, analyze, and execute the necessary reengineering steps. Often, no or only outdated models of such systems exist.Thus, a reverse engineering step is needed that recovers the system's components, subsystems, and connectors. However, reverse engineering methods are severely impacted by design deficiencies in the system's code base, e.g., they lead to wrong component structures.Therefore, Archimetrix enables the reengineer to detect the most relevant deficiencies with respect to a reverseengineered component-based architecture and supports him by presenting the architectural consequences of removinga given deficiency.

German UPA Qualitätsstandard für Usability Engineering - Behrenbruch, Kay; Bogner, Christian; Fischer, Holger Gerhard; Geis, Thomas; Geitner, Claudia; Heimgärtner, Rüdiger; Hofmann, Britta; Hunkirchen, Peter; Kluge, Oliver; Litzenberg, Britta; Molich, Rolf; Polkehn, Knut; et al.

Approximate Duality of Multicommodity Multiroute Flows and Cuts: Single Source Case - Kolman, Petr; Scheideler, Christian (Proceedings of the 23th ACM SIAM Symposium on Discrete Algorithms (SODA))
Given an integer h, a graph G = (V;E) with arbitrary positive edge capacities and k pairs of vertices (s1; t1); (s2; t2); : : : ; (sk; tk), called terminals, an h-route cut is a set F µ E of edges such that after the removal of the edges in F no pair si ¡ ti is connected by h edge-disjoint paths (i.e., the connectivity of every si ¡ ti pair is at most h ¡ 1 in (V;E n F)). The h-route cut is a natural generalization of the classical cut problem for multicommodity °ows (take h = 1). The main result of this paper is an O(h722h log2 k)-approximation algorithm for the minimum h-route cut problem in the case that s1 = s2 = ¢ ¢ ¢ = sk, called the single source case. As a corollary of it we obtain an approximate duality theorem for multiroute multicom-modity °ows and cuts with a single source. This partially answers an open question posted in several previous papers dealing with cuts for multicommodity multiroute problems.

Analyse, Konzeption und Implementierung von Aggregationsverfahren für Trinkwasserversorgungsnetze - Pischel, Daniel